2020
DOI: 10.1039/d0cp04923a
|View full text |Cite
|
Sign up to set email alerts
|

Visible-to-ultraviolet (<340 nm) photon upconversion by triplet–triplet annihilation in solvents

Abstract: Visible-to-UV upconversion shorter than 340 nm was achieved in organic solvents and the solvent dependent efficiency and photostability were elucidated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 70 publications
(75 reference statements)
1
47
0
1
Order By: Relevance
“…[39,40] The obtained η UC was more than twice larger than the previous record of 8.2% for the heavy metal-free vis-to-UV TTA-UC. [26] The tripletmediated UC mechanism was confirmed by a millisecond-scale decay of the UC emission (Fig. S3, ESI †).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…[39,40] The obtained η UC was more than twice larger than the previous record of 8.2% for the heavy metal-free vis-to-UV TTA-UC. [26] The tripletmediated UC mechanism was confirmed by a millisecond-scale decay of the UC emission (Fig. S3, ESI †).…”
mentioning
confidence: 83%
“…Since the first report of vis-to-UV TTA-UC in 2006, [11] various donor-acceptor combinations have been reported, but the efficiency had remained low for a long time. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our group has achieved the highest TTA-UC efficiency η UC of 20.5% (theoretical maximum: 100%) in 2020, which was twice as high as the previous record. [28] This is due to the use of an Ir-coumarin complex Ir(C6) 2 (acac) with strong absorption in the visible region and weak absorption in the UV region as a donor, as well as the discovery of an acceptor 1,4bis((triisopropylsilyl)ethynyl)naphthalene (TIPS-Nph) with high TTA and fluorescence efficiencies and a T 1 energy low enough to be sensitized by Ir(C6) 2 (acac).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Subsequently, UV-UC to a shorter wavelength than 340 nm is achieved in various solvents, including an IL by Murakami et al recently. [45] It is observed that UC-QYs and the photostability of sensitizer 10-butyl-2-chloro-9(10 h)-acridinone under continuous photoirradiation varies from solvent to solvent. It is found that UC-QYs are mainly governed by the solvent polarity, which varied the relative T 1 energy-level matching between the sensitizer and emitter, 2,6-di-tertbutyl naphthalene due to the solvatochromic shift imposed on sensitizer.…”
Section: Ils As a Sustainable Solvent Platform For Photon Ucmentioning
confidence: 99%
“…To develop non-volatile TTA-UC systems, earlier approaches have to introduce rubbery polymers or non-volatile liquids [5,24,[40][41][42][43][44][45][46][47][48] as matrices for the translational diffusion of molecules in the triplet excited state. Though translational molecular diffusion is certainly restricted in these viscous media, high intensity of excitation light is essential for getting upconverted light which is undesirable.…”
Section: Photon-upconverting Chromophoric Sustainable Ilsmentioning
confidence: 99%